TINJAUAN YURIDIS PERATURAN PEMERINTAH NOMOR 62 TAHUN 2019 TERHADAP KEPALA BADAN PENGUSAHAAN BATAM DIJABAT EX-OFFICIO OLEH WALI KOTA BATAM DIKAITKAN DENGAN PENYELENGGARAAN PEMERINTAHAN DAERAH - Fadhilah Fauzan; Mexsasai Indra; Adi Tiaraputri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Batam as an industrial area which development is carried out by the BatamIsland Industrial Area Development Authority agency, has also been expanded into anautonomous region which later give birth to the Batam City Government. The existence ofthese two government agencies then creates problems in the management of Batam Cityin the form of overlapping / dualism of authority. To overcome this problem, thegovernment then issued a new breakthrough by setting the Head of the Batam ConcessionAgency to be held ex-officio by the Mayor of Batam in the hope that the implementation ofhis duties and authority would be more effective. Therefore, the aim of this thesisresearch is first, the ex-officio determination of the Mayor of Batam from the point ofview of state administrative law. Second, the ex-officio implications by the Mayor ofBatam in public services. Third, the ideal arrangement for the relationship between theBatam City Government and the Batam Concession Agency.This type of research can be classified into the juridical sociological researchtype, because it wants to see the correlation between the law and what happens in thefield so as to reveal the effectiveness of the law's application. With the research locationlocated at the Batam Concession Agency and the Batam City Government, while thepopulation and sample are all parties related to the problem under study. This researchuses data sources in the form of primary data and secondary data, and data collectiontechniques are carried out by means of interviews, questionnaires and literature review.From the research, there are three main points that can be concluded. First,in fact, the ex-officio implementation by the Mayor of Batam is something that is justifiedin state administrative law. Second, the ex-officio implementation carried out by theMayor of Batam has no implication in resolving the problem of overlapping / dualism ofauthority that occurs in Batam City. Third, the ideal arrangement for the relationshipbetween the Batam City Government and the Batam Concession Agency is needednecessary to integrate the Batam, Bintan, and Karimun Free Trade Zone and Free PortExploitation Agency (BP BBK) by first issuing a Government Regulation as a form offurther regulation regarding the work relationship between the Batam City Governmentand the Batam Concession Agency. There is suggestion from author; first, the centralgovernment requires assertiveness in resolving issues of overlapping / dualism ofauthority that occur immediately issued a legal product in the form of a governmentregulation regarding the working relationship between the city government and theBatam concession agency. Second, accelerate the transfer of assets from the BatamConcession Agency to the Batam City Government.Keywords: Dualism – Authority – Public Service – Ex-officio